The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.4161/oxim.2.3.8804
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Provides Antioxidant Protection for Sperm Cryopreservation that May Offer New Consideration for Clinical Fertility

Abstract: Reactive oxygen species (ROS) are generated by sperm metabolism. While, ROS are required for maturation, capacitation and acrosome reaction, they also modify many peroxidable cellular compounds. There is production of ROS during cryopreservation and frozen spermatozoa are highly sensitive to lipid peroxidation (LPO). Antioxidants exert a protective effect on the plasma membrane of frozen bovine sperm preserving both metabolic activity and cellular viability. Manganese (Mn++) is proved to be a chain breaking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 37 publications
1
31
1
Order By: Relevance
“…The current results also agreed with Cheema et al [22] who found that the addition of Mn +2 (150 µM) to egg-yolkcitrate extender increased PC individual motility (58.3%) in comparison with those of control group (45%). Similar authors found that the addition of Mn +2 to Tris extender improved PC plasma membrane integrity (30.1%) in comparison with the control group (19.7%).…”
Section: Sajeda Mahdi Eidan Et Al: Influence Of Adding Manganese To supporting
confidence: 93%
“…The current results also agreed with Cheema et al [22] who found that the addition of Mn +2 (150 µM) to egg-yolkcitrate extender increased PC individual motility (58.3%) in comparison with those of control group (45%). Similar authors found that the addition of Mn +2 to Tris extender improved PC plasma membrane integrity (30.1%) in comparison with the control group (19.7%).…”
Section: Sajeda Mahdi Eidan Et Al: Influence Of Adding Manganese To supporting
confidence: 93%
“…Elegant work by Daly and colleagues has shown that tolerance to radiation and oxidative stress in a variety of bacterial species is due to accumulation of high levels of intracellular Mn, but low Fe (Daly 2006(Daly , 2009Daly et al 2007Daly et al , 2010Gross 2007;Granger et al 2011). In higher organisms, Mn treatment can prolong the life span and oxidative stress resistance in the simple metazoan, Caenorhabditis elegans, and also defend against reactive oxygen species (ROS) in the cryopreservation of sperm (Lin et al 2006;Bansal and Kaur 2009;Cheema et al 2009). …”
mentioning
confidence: 99%
“…The remainder are common signal transduction and receptor activities. Manganese is an anti-oxidant that prevents the damaging effects of oxidative stress (OS) and has been used to improve the in vitro environment to aid successful IVF or ICSI (Intra Cytoplasmic Sperm Injection) [Cheema et al 2009]. Our results show that the manganese ion transport activity is an important molecular function for sperm-egg interaction that if supressed finally leads to infertility.…”
Section: Molecular Function Analysismentioning
confidence: 67%